ANALISIS TEKNIS DAN EKONOMIS USAHA PERIKANAN TANGKAP DRIFT GILL NET DI PELABUHAN PERIKANAN SAMUDERA CILACAP - Hastuti, Indri; Bambang, Azis Nur; Rosyid, Abdul (Journal of Fisheries Resources Utilization Management and Technology, 2013)
The purpose of this study was to identify and analyze factors that influence the technical and economical aspects of drift gill net operation at Cilacap Fishing Port. The study was conducted in October-November 2012, at Cilacap Fishing Port. The material used in this study is a business operation unit of drift gill nets that are still actively operating with this type of material monofilament and multifilament fishing gear, with a number of their ships - each 10 vessels <30 GT. The method used in this research is descriptive method using a case study approach. The results of this research showed that the technical aspects between multifilament and monofilament drift gill net have differences in terms of net material and operation, namely for drift gill net monofilament made of chord (winding yarn) and operated by swept away by a circular position while the drift gill net multifilament nylon twisted 12-13 strings millennium, and operation of drift gill net multifilament is simply washed away by the stretched position, and the average gain drift gill net multifilament higher than monofilament drift gill net. The analysis shows the feasibility of drift gill net multifilament and monofilament drift gill net worth to be continued visits from the NPV 563,712,463 with 112,415,740; B / C ratio of 1,7 with 1,1; IRR of 74% to 19%, and PP 2 years 18 days with 2 years 6 month.